In situ electrical characterization of palladium-based single electron transistors made by electromigration technique - Arzubiaga, L. (2014)
We report the fabrication of single electron transistors (SETs) by feedback-controlled electromigration of palladium and palladium-nickel alloy nanowires. We have optimized a gradual electromigration process for obtaining devices consisting of three terminals (source, drain and gate electrodes), which are capacitively coupled to a metallic cluster of nanometric dimensions. This metal nanocluster forms into the inter-electrode channel during the electromigration process and constitutes the active element of each device, acting as a quantum dot that rules the electron flow between source and drain electrodes. The charge transport of the as-fabricated devices shows Coulomb blockade characteristics and the source to drain conductance can be modulated by electrostatic gating. We have thus achieved the fabrication and in situ measurement of palladium-based SETs inside a liquid helium cryostat chamber.